Effect of hing glucose induced hyperglycemia on Viral Haemorrhagic Septicaemia Virus (VHSV) infection in Adult zebrafish / Tran Van Cuong, Nguyen Thi Thoa - Tran, Van Cuong
The data also demonstrated that adult zebrafish fed high glucose a VHSV challenge highly increased in Mrna levls of inflamatory cytokines as well as in the expression level of endoplasmic reticulin stress